The Effect of the Learners’ Perception on Motivation, Teaching Method, Discipline, Learning Style, and Learning Atmosphere toward Writing Achievement at İslamic University Students - Elhawwa, Tazkiyatunnafs (Universitas Negeri Semarang, 2022)
The research attempted to measure the variables predicted to be the factors contributing to the success: Motivation (x1), Teaching Method (x2), Discipline (x3), Learning Style (x4), and Learning Atmosphere (x5). The study applied expost facto design. It recruited 30 participants. The multiple regression analysis was used. The finding highlighted that that F (5, 24) = 77.736, p=0.000. It was stated that all five variables simultaneously gave effect to learners’ writing achievement. The higher all variables perceived by the learners, the higher writing achievement would be. Then, the R value was 0.970, indicating a high correlation amongst the varables. The result of R2 was 0.942, meaning that the overall regression of variables gave contribution to learners’ writing achievement about 94.2%. Meanwhile, each variable: Motivation (49, 63%), Teaching Method (26.02%), Discipline (5.77%), Learning Style (-3.13%), and Learning Atmosphere (18.74%) gave contribution to writing achievement.